ABOUT ONE CLASS OF COMBINATORY CONFIGURATIONS - I. P. Kadiev; P. A. Kadiev (Вестник Дагестанского государственного технического университета: Технические науки)
The articles descry a new class combinatory configurations - circulate of matrixes and methods them formed.